Asset-Based Community Development: Pengembangan Produk Pertanian Sari Jeruk Khas Dusun Precet - Karisma, Ria Dhea Nur; Widayani, Heni; Naschicuddin, Achmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Oranges are a type of fruit that contains lots of vitamin C and fiber. One of the citrus producing places in Malang is Dusun Precet, which is part of Sumbersekar Village. The abundant citrus plantation products in Precet Hamlet have not been further processed by the residents, so the price falls during the harvest season. Farmers left some of it to rot in the garden, because the cost of picking during the harvest season is more expensive than the selling prices. Whereas the oranges can have a higher selling value if it is processed into orange juice products. The Asset-Based Community Development (ABCD) strategy was implemented by the UIN Maulana Malik Ibrahim Malang team in the form of training activities for processing orange juice products. The basic mindset in ABCD theory on assisted objects has five key steps, namely discovery, dream, design, define, and destiny. Assets that support the ABCD theory in assisted objects are categorized into four, namely human assets, natural assets, economic assets, and social assets. Dusun Hamlet is potential place to process citrus fruits becomes fresh orange juice that can be consumed by the wider community. Moreover, orange juice is produced without using preservatives so that it can be consumed by various ages.